2018
DOI: 10.1155/2018/1572037
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of the Stomatognathic System, after the Treatment of Edentulous Patients, with Different Methods of Establishing the Centric Relation

Abstract: The study compares subjective experiences of patients, wearing complete dentures. Two different methods of determining a centric relation were performed: the traditional method using wax occlusal rims and the Gerber method, based on gothic arch tracings. The success rate of establishing a centric relation in both methods was evaluated (rentgenodiagnostics). The influence of the method used to obtain the centric relation on patients' stomatognathic system (condyle centralization, pain) was also evaluated. Bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…where e is the effectiveness resulting from the calculations for this study, f (7 or 9) is the final value given by the authors of the given report and i (6 or 8) is the initial value extracted from the same report. These calculations provided further data: (10) improvement in mandibular abduction; (11) reducing the value of joint pain [29][30][31][32]. In the case of mandibular mobility, values greater than 100% indicated good results of the therapy, and in the domain of pain, values less than 100% indicated a decrease in symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…where e is the effectiveness resulting from the calculations for this study, f (7 or 9) is the final value given by the authors of the given report and i (6 or 8) is the initial value extracted from the same report. These calculations provided further data: (10) improvement in mandibular abduction; (11) reducing the value of joint pain [29][30][31][32]. In the case of mandibular mobility, values greater than 100% indicated good results of the therapy, and in the domain of pain, values less than 100% indicated a decrease in symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies 16,19,36,52,53 have reported that graphic CR recording techniques represent a valid reference as a comparison parameter, because the patient must perform lateral and protrusive movements to apply them. Their reproducibility tends to be more reliable, considering that there is an orthoprosthetic (muscular) balance, which requires the patient to master the movements of the mandibular jaw 33,58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Nitecka-Buchta et al evaluated the stomatognathic system following edentulous patients' treatment with various techniques of establishing the centric relation [13]. The study compared patients' subjective experiences with complete dentures.…”
Section: Discussionmentioning
confidence: 99%
“…The studies involving complete denture as a treatment therapy for treating TMDs that were covered in the present systematic review are the studies by Engel et al in 1995 [ 9 ], Wolfart et al in 2005 [ 10 ], Zuccolotto et al in 2007 [ 11 ], Yu et al in 2013 [ 12 ] and Nitecka-Buchta et al in 2018 [ 13 ] (Table 2 ).…”
Section: Reviewunclassified